THE STUDY ABOUT THE IMPACT OF EMOTIONAL TENSION ON THE STUDENTS’ EXCITEMENT AND MEMORY PROCESSES - Karamova Natavan; Hakverdieva Zumrud; Akbarova Khadija; Kazenferov Eldar (World Science, 2019)
Studies have investigated the effect of emotional stress on anxiety and memory processes. The object of the study was first-year students. Psychophysiological research methods have been used. Under the influence of emotional stress, there were changes in memory and an increase in anxiety levels.